2000
DOI: 10.1007/bf02682259
|View full text |Cite
|
Sign up to set email alerts
|

Role of eicosanoids in regulation of macrophage phagocytic functions by platelet-activating factor during endotoxic shock

Abstract: We studied the role of eicosanoids in the regulation of macrophage phagocytic functions by products secreted in heterogeneous populations of macrophages and platelet-activating factor during endotoxic shock. Phagocytic activity depended on the metabolism of arachidonic acid in target macrophages and the ratio between its cyclooxygenase and lipoxygenase metabolites produced by heterogeneous populations of macrophages and affecting target cells. The regulatory effect of platelet-activating factor on phagocytosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In addition to acting as phagocytic and antigen-presenting cells, macrophages can promote or modulate inflammation through classical and alternative activation pathways, respectively (46). Under different stimuli, macrophages produce multiple lipid mediators including lysophospholipids and eicosanoids, and these bioactive lipids can impact cells of surrounding tissues and the function of macrophages themselves (20,36,47). A major source of lyso- iPLA 2 ␤ and Macrophage Polarization OCTOBER 28, 2016 • VOLUME 291 • NUMBER 44 phospholipids and arachidonic acid, the common eicosanoid precursor, is the lipase activity of PLA 2 s (19).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to acting as phagocytic and antigen-presenting cells, macrophages can promote or modulate inflammation through classical and alternative activation pathways, respectively (46). Under different stimuli, macrophages produce multiple lipid mediators including lysophospholipids and eicosanoids, and these bioactive lipids can impact cells of surrounding tissues and the function of macrophages themselves (20,36,47). A major source of lyso- iPLA 2 ␤ and Macrophage Polarization OCTOBER 28, 2016 • VOLUME 291 • NUMBER 44 phospholipids and arachidonic acid, the common eicosanoid precursor, is the lipase activity of PLA 2 s (19).…”
Section: Discussionmentioning
confidence: 99%
“…10 -12 Macrophage studies have revealed involvement of cyclooxygenases (COX) and prostaglandins as a result of PLA 2 activity in the regulation of phagocytosis. 8,13,14 Most evident is the role of cPLA 2 and sPLA 2 , group V in regulation of phagocytosis. 7,15 Recent studies furthermore indicate a role of iPLA 2 in phagocytosis since PLA 2 -induced cleavage of PC in dying cells leads to phagocytosis of these by adjacent macrophages.…”
mentioning
confidence: 97%